Esporotricosis en Argentina: análisis clínico y epidemiológico Sporotrichosis in Argentina: clinical and epidemiological analysis Esporotricosis en Argentina - Santiso, Gabriela Maria (2023)
Introduction. Sporotrichosis is an implantation mycosis caused by Sporothrix spp. It is distributed worldwide and can be found in vegetation and soil. The most frequent route of infection is by trauma with elements contaminated with fungal propagules. Since domestic cats are the most affected animals and can transmit this infection to humans, sporotrichosis is considered a zoonosis. Clinical presentations include nodular lymphangitis, fixed cutaneous, pulmonary (rare), and disseminated (exceptional). Objectives. To analyze the epidemiology of sporotrichosis in Argentina during 2010 and 2022. To describe the clinical presentation, diagnostic methods, and treatment of cases diagnosed during this period. To know the circulating genotypes and to observe possible associations with the geographic location where the infection was acquired. Materials and methods. Analytical, retrospective, and observational study. We analyzed the medical records of patients with sporotrichosis from 12 health institutions in Argentina, between 2010 and 2022. Results. We present 54 cases in which the most frequent clinical form was nodular lymphangitis, and the treatment of choice was itraconazole. Conventional diagnosis was made in all cases. Culture of clinical samples was more sensitive than direct examination because it allowed the isolation of Sporothrix spp. in all 54 cases. Molecular identification was performed in 22 cases, with Sporothrix schenkii sensu stricto being the most frequently isolated species. Conclusions. This study allowed to know the epidemiology of this mycosis in Argentina, as well as the availability of diagnostic methods and the treatment of choice.